Commentary on Aristotle, ›Nicomachean Ethics‹ - Georgius <Pachymeres> (2022)
This volume includes the first critical edition of George Pachymeres’ Commentary on Aristotle’s Nicomachean Ethics. An English translation of the Byzantine text and an extensive introduction on philosophical and philological matters relating to the contextualisation, interpretation and textual transmission of the work are also provided. In addition, the book encompasses the edition of diagrams and scholia accompanying Pachymeres’ exegesis.